PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA SDM KONSTRUKSI - Ainanur, Irda (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2013)
Leadership in construction services company is important in an age of modern organization there is want to democratization in the implementation of the human resource construction work and leadership in the construction company . there is possibelities cause of bad leadership style is a decrease in the performance of human resources will impact at the performance of the human resource construction